Assessment and association of tobacco affecting oral health of workers of a factory - Singhvi, Shreyans D.; Singh, Preksha T.; Khan, Rafe (International Journal Of Community Medicine And Public Health, 2020)
Background: Occupational health diseases have become severe in the present scenario of the world. In our study, we assessed the oral health of the workers along with association of factors affecting the oral health. The factor mainly studied was tobacco consumption. Thus, the study is extremely important to study the oral health of workers as they are more prone to develop oral lesions and less likely to access medical help for the same. Methods: A cross sectional study of 240 workers of a textile factory was studied using a structural self-constructed questionnaire was used in the study. A well informed verbal consent was taken by the participants of the study. It had open and closed ended questions. Further, oral health of the workers were assessed with current and past history, medical history and addiction his-tory. Oral health was checked and the oral lesions of the participants were studied. Oral le-sions as well as pre-malignant and malignant oral lesions were studied. Results: During the study it was found that maximum participants reported of tobacco chewing (50.41%), while males reported of tobacco addiction history more than females. Oral health was assessed and oral lesions were examined. 62% of the participants had no oral lesions while 38% participants presented with oral lesions. Positive association between tobacco consumption and oral lesions was found. Conclusions: Addiction history is very important during examination of oral health, as tobacco and alcohol are major factors affecting oral health.